Smoking, mortality, access to diagnosis, and treatment of lung cancer in Brazil - Mônica Rodrigues Campos; Jessica Muzy Rodrigues; Aline Pinto Marques; Lara Vinhal Faria; Tayná Sequeira Valerio; Mario Jorge Sobreira da Silva; Debora Castanheira Pires; Luisa Arueira Chaves; Carlos Henrique Dantas Cardoso; Silvio Rodrigues Campos; Isabel Cristina Martins Emmerick (Universidade de São Paulo, 2024)
ABSTRACT INTRODUCTION Lung cancer (LC) is a relevant public health problem in Brazil and worldwide, given its high incidence and mortality. Thus, the objective of this study is to analyze the distribution of smoking and smoking status according to sociodemographic characteristics and disparities in access, treatment, and mortality due to LC in Brazil in 2013 and 2019. METHOD Retrospective study of triangulation of national data sources: a) analysis of the distribution of smoking, based on the National Survey of Health (PNS); b) investigation of LC records via Hospital-based Cancer Registry (HCR); and c) distribution of mortality due to LC in the Mortality Information System (SIM). RESULTS There was a decrease in the percentage of people who had never smoked from 2013 (68.5%) to 2019 (60.2%) and in smoking history (pack-years). This was observed to be greater in men, people of older age groups, and those with less education. Concerning patients registered in the HCR, entry into the healthcare service occurs at the age of 50, and only 19% have never smoked. While smokers in the population are mainly Mixed-race, patients in the HCR are primarily White. As for the initial stage (I and II), it is more common in White people and people who have never smoked. The mortality rate varied from 1.00 for people with higher education to 3.36 for people without education. Furthermore, White people have a mortality rate three times higher than that of Black and mixed-race people. CONCLUSION This article highlighted relevant sociodemographic disparities in access to LC diagnosis, treatment, and mortality. Therefore, the recommendation is to strengthen the Population-Based Cancer Registry and develop and implement a nationwide LC screening strategy in Brazil since combined prevention and early diagnosis strategies work better in controlling mortality from the disease and continued investment in tobacco prevention and control policies.